Drivers of female labour force participation in urban India during India's Economic Boom - Janneke Pieters; Stephan Klasen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In the past twenty years, India's economy has grown at increasingly faster rates and now belongs to the fastest-growing economies in the world. One would think that in such economic conditions, women are increasingly being pulled into the labour force by attractive pay and employment conditions. This paper examines trends and drivers of female labour force participation in urban India between 1987 and 2004; we do this using aggregate and unit level data and estimate econometric participation models. Our paper shows a much more nuanced picture than one might expect. While we find, as expected, that cultural and social factors strongly influence female labour force participation rates, among the somewhat unexpected findings are:- Only in the period between 1999 and 2004 did female labour force participation rates increase in urban areas; before, rates remained flat due to offsetting effects of increases among some groups and decreases among others;- At lower levels of education, increases in female labour force participation are driven more by distress than by increasing economic opportunities; this is linked to stagnant real wages at this level;- At mid-levels of education, the income effect of rising male incomes served to reduce female labour force participation rates considerably; while we find some evidence of a positive own wage effect, the income effect of husband's earning remains a very strong driver of female labour force participation;- Only at the highest education levels do we see some evidence from pull factors drawing women into the labour force at attractive employment and pay conditions; this affects, by 2004, only a tiny minority of India's women.As a result, the economic boom has offered remarkably few opportunities to women in India. In fact, for all but the very well-educated, it appears that the labour market conditions have not improved at all, or even deteriorated.
Keywords: 330